Hydroxychloroquine Does Not Function as a Direct Zinc Ionophore - Oisín N. Kavanagh; Shayon Bhattacharya; Luke Marchetti; Robert Elmes; Finbarr O'Sullivan; John P. Farragher; Shane Robinson; Damien Thompson; Gavin M. Walker (MDPI AG, 2022)
Drug-mediated correction of abnormal biological zinc homeostasis could provide new routes to treating neurodegeneration, cancer, and viral infections. Designing therapeutics to facilitate zinc transport intracellularly is hampered by inadequate concentrations of endogenous zinc, which is often protein-bound in vivo. We found strong evidence that hydroxychloroquine, a drug used to treat malaria and employed as a potential treatment for COVID-19, does not bind and transport zinc across biological membranes through ionophoric mechanisms, contrary to recent claims. In vitro complexation studies and liposomal transport assays are correlated with cellular zinc assays in A549 lung epithelial cells to confirm the indirect mechanism of hydroxychloroquine-mediated elevation in intracellular zinc without ionophorism. Molecular simulations show hydroxychloroquine-triggered helix perturbation in zinc-finger protein without zinc chelation, a potential alternative non-ionophoric mechanism.